2011
DOI: 10.1371/journal.pone.0025908
|View full text |Cite
|
Sign up to set email alerts
|

Adhesion Protein VSIG1 Is Required for the Proper Differentiation of Glandular Gastric Epithelia

Abstract: VSIG1, a cell adhesion protein of the immunoglobulin superfamily, is preferentially expressed in stomach, testis, and certain gastric, esophageal and ovarian cancers. Here, we describe the expression patterns of three alternatively spliced isoforms of mouse Vsig1 during pre- and postnatal development of stomach and potential function of Vsig1 in differentiation of gastric epithelia. We show that isoforms Vsig1A and Vsig1B, which differ in the 3′untranslated region, are expressed in the early stages of stomach … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(34 citation statements)
references
References 22 publications
(19 reference statements)
2
32
0
Order By: Relevance
“…The two main isoforms (NM_030181 and XM_006528630) were relatively abundant in the mouse stomach and were highly expressed at the later stages of development (Supplementary Fig. 4d ), which is consistent with a previous study 48 . If validated, these previously undetected peptides and their associated protein isoforms will identify new players in stomach development and developmental biology.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The two main isoforms (NM_030181 and XM_006528630) were relatively abundant in the mouse stomach and were highly expressed at the later stages of development (Supplementary Fig. 4d ), which is consistent with a previous study 48 . If validated, these previously undetected peptides and their associated protein isoforms will identify new players in stomach development and developmental biology.…”
Section: Resultssupporting
confidence: 92%
“…ANXA10 is a calcium- and phospholipid-binding protein expressed in the gastric mucosa 47 . VSIG1 is a cell adhesion protein required for the proper differentiation of glandular gastric epithelia 48 . CLDN18 is a gastric epithelium-associated claudin 49 .…”
Section: Resultsmentioning
confidence: 99%
“…Other genes exhibiting similarly large sex specific fold-changes included keratin 36 ( KRT36 ) which was expressed 6.6-fold higher in the reticulum of male relative to female sheep and VSIG1 (V-Set and immunoglobulin domain containing 1), which is required for the differentiation of glandular gastric epithelia [ 93 ]. VSIG1 showed 4-fold greater expression in the female pylorus relative to the male.…”
Section: Resultsmentioning
confidence: 99%
“…In a mouse model, the cytoplasmic tail domain of VSIG1 binds to ZO‐1, an important molecule of tight junctions, through the Ser/Thr‐X‐Val/Ile motif . However, another mouse study showed that VSIG1 expressed in gastric epithelial cells was distributed along the lateral membrane of the glandular epithelia in a distribution pattern similar to adherens junctions, and that VSIG1 did not colocalize with ZO‐1 . Moreover, this motif is not present in human VSIG1.…”
Section: Discussionmentioning
confidence: 96%